The Impact of Obesity on Periodontal Health Status in Adolescent Iraqi Students - Al-Karawi, Sarah Ihsan; Mahmood, Athraa Ali; Hassan, Ban Karem (Brazilian Dental Science, 2021)
Objetive: The aim of this study was to estimate the effect and association of obesity on the periodontal health status of middle school students. Materials and Methods: This study included 180 secondary school students aged 12- 15 years from Baghdad City in the survey. BMIfor-age (body mass index for age) was utilized to detect overweight and obesity. Furthermore, periodontal screening records (PSR) index was performed to evaluate the oral hygiene and periodontal condition of the subjects. Chisquare tests and two-way ANOVA were used for statistical analyses. Results: A highly significant association of BMI-for-age with periodontal health (codes 0, 1, 2, and 3) was observed. The association of gender and periodontal health was highly significant in code 3, significant in codes 0 and 1, and it was not significant in code 2. Additionally, the ANOVA test revealed that the effects of gender and BMI-for-age on periodontal health were significant. In contrast, the effect of the interaction between gender and BMI-for-age on periodontal health was not it was not significant. Conclusions: In adolescents, bad oral hygiene was correlated with extra body fat indicators. Therefore, oral health preventive schedules should take into consideration the relationship between periodontal condition and overweight/obesity in teenagers. Keywords Obesity; Body mass index; Periodontal disease; Oral health status.